Inkheart : movie novelization - Mason, Jane.; Hines-Stephens, Sarah; Funke, Cornelia Caroline (New York : Scholastic, 2009)
Meggie learns that her father's gift of being able to bring to life people and things he reads about in books has been passed on to her and tries to use the power to rescue her mother, who was pulled into the pages of a fantasy novel when Meggie was a child.
"From the screenplay by David Lindsay-Abaire."
5.0
3-6
Keywords: Books and reading -- Juvenile fiction; Characters in literature -- Juvenile fiction; Magic -- Juvenile fiction; Bookbinding -- Juvenile fiction; Authorship -- Juvenile fiction; Books and reading -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Bookbinding -- Fiction; Authorship -- Fiction; Books and reading -- Fiction; Characters and characteristics in literature -- Fiction; Magic -- Fiction; Bookbinding -- Fiction; Authorship -- Fiction